Phasenadaptierte Therapie akuter Bandverletzungen des Sprunggelenkes beim Sportler - Petersen, W.; Liebau, C.; Brüggemann, G. P.; Ellermann, A.; Best, R.; Gösele-Koppenburg, A.; Rembitzki, I. V. (Sport-Orthopädie - Sport-Traumatologie, 2010)
The lateral ankle sprain is the most frequent injuries in athletes. Many patients suffer from chronic complaints after an acute ankle sprain despite treatment. The risk of a second ankle sprain is 2-5 fold increased, especially in athletes. There is no correlation between severity of injury and chronic problems. Especially patients with a grade I sprain have a higher risk for chronic problems than patients with a severe injury. Therefore prevention should play an important role. The healing process of the torn ligaments can be divided in three different phases (inflammatory phase, proliferation phase, and regenerative phase). Clinical studies could demonstrate advantages for operative and non operative treatment. Regarding possible complications of surgery treatment of choice is non operative. For non operative treatment stabilization of the ankle can be achieved with plaster casts, stable and semi rigid orthosis, tape or elastic bandages. The amount of stabilization should be adapted to the different phases of ligament healing. Furthermore there is some evidence that the non operative treatment should be supported by a sensomotoric training program.